The absurd workplace : how absurdity is normalized in contemporary society and the workplace /: how absurdity is normalized in contemporary society and the workplace. (2022) - Bal, Matthijs; Brookes, Andy; Hack-Polay, Dieu Donné; Kordowicz, Maria; Mendy, John
No abstract available